Annular Bounds for the Zeros of a Polynomial - Le Gao; N. K. Govil (International Journal of Mathematics and Mathematical Sciences)
The problem of obtaining the smallest possible region containing all the zeros of a polynomial has been attracting more and more attention recently, and in this paper, we obtain several results providing the annular regions that contain all the zeros of a complex polynomial. Using MATLAB, we construct specific examples of polynomials and show that for these polynomials our results give sharper regions than those obtainable from some of the known results.